Probabilistic Behaviour of a Transit System Having Mixed Networks under Pre-Emptive Resume Repair Policy - Viresh Sharma (International Journal of Advanced Science and Technology, 2018)
The Author has considered a complex system consisting of two subsystem A and B connected in series subsystem A and B are connected in series. Sub-system A consists of N non-identical components in series, while sub-system B consists of four identical components in parallel redundancy.